Analisis Pengaruh Green Product dan Green Packaging Terhadap Brand Loyalty Melalui Brand Image Sebagai Variabel Intervening (Studi Pada Pengguna Produk Tupperware di Surabaya) - nur rahmawati; Nurul Azizah (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2022)
The development of the business industry is rapidly increasing the consumption pattern of the community towards the use of products in the midst of environmental issues that become problems in human life. The consequence of this is that the accumulation of waste, one of which is plastic, can cause environmental damage. The application of green marketing is an effort to achieve global competitiveness through product development through green products and green packaging. The purpose of this study was to analyze the effect of green products and green packaging on brand loyalty through brand image as an intervening variable for Tupperware products. This type of research is a quantitative research. The research population is users of Tupperware products in Surabaya. While the research sample is 150 respondents who are determined through non-probability sampling method. The data collection method used a questionnaire. The data analysis technique used is descriptive statistics and inferensial with smart pls 3.0. Based on the results of the study, it was found that green products had a positive and significant effect on brand image. Green packaging has a positive and significant effect on brand image. Brand image has a positive and significant effect on brand loyalty. Green product has a positive and significant effect on brand loyalty. Green packaging has a positive but not significant effect on brand loyalty. Green products have a negative and positive effect on brand loyalty through brand image. Green packaging has a positive and significant effect on brand loyalty through brand image.